1970
DOI: 10.3126/jnps.v30i1.2456
|View full text |Cite
|
Sign up to set email alerts
|

Infection of <i>Cyclospora cayetanensis</i> in Diarrhoeal Children of Nepal

Abstract: Introduction: Cyclospora cayetanensis is a coccidian parasite that causes recurrent gastroenteritis among children living under poor sanitary condition and adults from industrialized countries who lived or traveled in endemic developing countries. Methods: A total of 1842 stool specimens from gastroenteritis patients were examined between March 2006 to February 2007 and collected various types of faecal specimens from human, animals and samples of water and green leafy vegetables. Results: Of 1842 stool specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 13 publications
0
24
2
1
Order By: Relevance
“…Different Brazilian regional studies have also reported the presence of Giardia spp., Cryptosporidium spp., and Cyclospora spp. in dogs and cats (13) (14) . Giardia spp.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Different Brazilian regional studies have also reported the presence of Giardia spp., Cryptosporidium spp., and Cyclospora spp. in dogs and cats (13) (14) . Giardia spp.…”
mentioning
confidence: 99%
“…Giardia spp., Cryptosporidium spp., and Cyclospora spp. have been found throughout the world in recreational water, including chlorinated water, because they are resistant to adverse environmental conditions (12) (13) . Moreover, the identifi ed parasites have a high zoonotic potential, with the capacity to develop in human and animal hosts (2) .…”
mentioning
confidence: 99%
“…Parasites have been detected in irrigation water in numerous studies (Robertson and Gjerde, 2001;Robertson et al, 2002;Thurston-Enriquez et al, 2002;Tram et al, 2008;Andoh et al, 2009;Mota et al, 2009;Sherchan et al, 2010;Amorós et al, 2010). Parasites have been detected in irrigation water in numerous studies (Robertson and Gjerde, 2001;Robertson et al, 2002;Thurston-Enriquez et al, 2002;Tram et al, 2008;Andoh et al, 2009;Mota et al, 2009;Sherchan et al, 2010;Amorós et al, 2010).…”
Section: Preharvest Control Measuresmentioning
confidence: 99%
“…The irrigation of crops with contaminated water or the use of contaminated water to mix pesticides or wash produce are other possible sources. Numerous surveillance studies have, in fact, concluded that irrigation water was the source of contam ination (4,32,34), and this conclusion has been supported by the detection of parasitic organisms in irrigation water (42,45,47). Amahmid et al (4) concluded that irrigation of crops with raw waste water leads to contamination with Giardia and the nematode Ascaris.…”
mentioning
confidence: 99%
“…Contamination of produce by livestock, either through direct access or through the application of manure to crop lands, has also been proposed (14,35,43). Other possible sources of contamination of vegetables with intestinal parasites include insects and rodents, other wildlife, market vendors, and even contam inated money handled by food workers (14,24,45,46).…”
mentioning
confidence: 99%